Analisis Pemberdayaan Perempuan Dalam Industri Kain Jumputan - Mohd Aji Isnaini; Hasril Atieq Pohan; Mutiara September (Journal of Innovative and Creativity, 2025)
Collection, and Jumputan Bang Syaiful. The results of the study show that women's empowerment in this industry is carried out through technical skills training, providing access to capital and financing, business assistance, and active involvement of women in decision making. Women are also given space to innovate and manage their businesses independently. This empowerment has a positive impact on improving women's economic welfare, self-confidence, and bargaining position in the family and society.However, women's empowerment still faces various obstacles such as limited capital, lack of advanced training, limited access to technology and market information, and the double burden of work and household responsibilities. In conclusion, women's empowerment in the tie-dye industry in Tuan Kentang not only contributes to improving the family economy, but also helps preserve local culture. Therefore, further support is needed from the government, financial institutions, and local communities so that women's potential in this sector can be optimized sustainably.